2018
DOI: 10.1007/s11596-018-1867-4
|View full text |Cite
|
Sign up to set email alerts
|

Sanguinarine Attenuates Lipopolysaccharide-induced Inflammation and Apoptosis by Inhibiting the TLR4/NF-κB Pathway in H9c2 Cardiomyocytes

Abstract: The inflammatory response is involved in the pathogenesis of the most common types of heart disease. Sanguinarine (SAN) has various pharmacological properties such as anti-inflammatory, antioxidant, antibacterial, antitumor, and immune-enhancing properties. However, few studies have investigated the effects of SAN on lipopolysaccharide (LPS)-induced inflammatory and apoptotic responses in H9c2 cardiomyocytes. Therefore, in this study, H9c2 cells were co-treated with SAN and LPS, and the mRNA levels of pro-infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 22 publications
0
19
0
1
Order By: Relevance
“…Treatment of ALL cells with sanguinarine was reported to cause apoptosis through loss of mitochondrial membrane potential (MMP), activation of caspase pathways and generation of reactive oxygen species (ROS) (15). Furthermore, sanguinarine-induced apoptosis is strongly associated with multiple signaling pathways including the mitogen-activated protein kinase (MAPK) (17), phosphoinositide-3-kinase/protein kinase B (18), Wnt/β-catenin (19) and Toll-like receptor 4/nuclear factor-κ B signaling pathways (20). However, to the best of our knowledge, few studies have focused on examining its efficacy on HLEs and its underlying mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of ALL cells with sanguinarine was reported to cause apoptosis through loss of mitochondrial membrane potential (MMP), activation of caspase pathways and generation of reactive oxygen species (ROS) (15). Furthermore, sanguinarine-induced apoptosis is strongly associated with multiple signaling pathways including the mitogen-activated protein kinase (MAPK) (17), phosphoinositide-3-kinase/protein kinase B (18), Wnt/β-catenin (19) and Toll-like receptor 4/nuclear factor-κ B signaling pathways (20). However, to the best of our knowledge, few studies have focused on examining its efficacy on HLEs and its underlying mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…14 As a transcriptional activator, NF-jB increases the expression levels of downstream genes, including the inflammatory cytokine genes TNFa and TLR4 and the apoptosis-related genes AIF and BAX, and provokes a rapid inflammatory response and cell apoptosis. 14,16,17 However, the mechanism by which SSRIs induce DED is not clear. Further studies are necessary to explore the effects and mechanism of SSRIs in DED.…”
mentioning
confidence: 99%
“…A number of studies have shown the therapeutic potential of SNG over a range of human pathological and toxicological conditions including cancer; for example, lung cancer [25], cervical cancer [26], gastric cancer [27,28], liver cancer [29,30], multiple myeloma [19], acute lymphoblastic leukemia [31], prostate cancer [32], colorectal cancer [33], ovary cancer [34] and pancreatic cancer [35]. Recently Achkar et al [36] extensively reviewed the anticancer features of SNG and, additionally, antioxidant/anti-inflammatory [37][38][39], antifungal [40,41], antibacterial [42,43], anthelmintic [44] and other pharmacological activities of SNG have also been reported. SNG has been shown to suppress stemness of pancreatic cancer stem cells [45] and, interestingly, also to exert anticarcinogenic potential via modulating expression and functioning of noncoding RNAs [28,34].…”
Section: Introductionmentioning
confidence: 99%